Residual effect of organic fertilization on radish production - Lanna, Natália B. L. [UNESP]; Silva, Priscilla Nátaly L. [UNESP]; Colombari, Lidiane F. [UNESP]; Corrêa, Carla Veronica [UNESP]; Cardoso, Antonio Ismael Inácio [UNESP] (FapUNIFESP (SciELO), 2018)
This research aimed to evaluate the residual effect of doses of organic compost on the radish production, as well as its effect on soil chemical properties. Experiments were conducted in two areas (“low” and “high” soil fertility). Prior to this, these areas were first used to evaluate the influence of organic compost doses on endive production. After harvesting endive, radish seeds were sown into the same plots used for endive to evaluate the residual effect. The six treatments consisted of organic compost doses (0, 35, 70, 105, 140 and 175 t ha-1), evaluated in a complete block experimental design, with four replications. Vegetative characteristics of radish plants (shoot, root and total fresh and dry matter weight, plant height and root diameter) and soil characteristics (macronutrient content, pH, H+Al, organic matter, sum of bases, cation exchange capacity and base saturation) in two dates (11 days after the endive transplant and at the end of the radish cycle) were evaluated. No significant difference was observed for all doses of organic compost in the “low” soil fertility area, obtaining only non-commercial roots (average fresh weight of 5.01 g per root). In the “high” soil fertility area, the higher the organic compost doses, the higher the values of most vegetatitve characteristics of radish plants and the chemical properties of the soil in both dates. For root fresh weight, the values ranged from 4.63 to 9.15 g in the control without organic compost and in the highest dose, respectively. In “high” soil fertility area, only K content in soil has not remained high for all organic compost doses, and the values ranged from 2.8 and 4.5 mmolcdm-3, in control without organic compost and in the highest dose, respectively. The residual effect of organic compost was confirmed by the increasing on the radish production in initial “high”soil fertility area.
Efeito residual da adubação com composto orgânico na produção de rabanete
Keywords: Crop rotation; Nutrient; Raphanus sativus; Soil fertility